PENGARUH RASIO KEUANGAN, AKSI KORPORASI DAN FAKTOR FUNDAMENTAL EKONOMI MAKRO TERHADAP HARGA SAHAM - Indra Saputra; Veny Veny; Sekar Mayangsari (Jurnal Magister Akuntansi Trisakti, 2018)
This study aimed to examine the effect of return on assets, debt to equity ratio, earning per share, price earnings ratio, dividend per share, interest rate, and exchange rate to stock price. The population of this research is publicly traded manufacturing companies listed in Indonesia Stock Exchange in the period from 2013- 2016. Samples were selected by purposive sampling method to acquired 90 companies. This study uses white regression using SPSS. The results showed that the return on assets, debt to equity ratio, dividend per share, interest rate, and exchanges rate have no effect on stock price; while earning per share, price earnings ratio, and dividend per share have a significant positive effect on stock price.